OPTIMALISASI ALOKASI LAHAN RUMAH TANGGA PETANI HUTAN RAKYAT DI DESA WONGKAI MINAHASA TENGGARA - Gracecia Th. J. Antou; Hengki D. Walangitan; Theodora M. Katiandagho (COCOS, 2015)
ABSTRACT OPTIMIZATION ALLOCATION OF FOREST LAND FARMER HOUSEHOLDS IN THE VILLAGE OF WONGKAI THE SOUTHEAST MINAHASA  The objective of research is the description the planting patterns of community forests and to analysis planting patterns that produce highest income for the haousehold income in the Wongkai based on farm area.  The research was conducted in June 2015. The methods used in this research was survey and purposive sampling.  The descriptive method is used is explained technical aspects planting patterns; where as linear program was used to determine planting patterns that produce highest income.  Results showed that farmer’s implemented monoculture and mixed planting patterns.  For the more linear program analysis showed that highest income was shown by mahogany planting in 0.11  area, champaca in 3 ha area, nantu in 3,12 ha area, teak in 1 ha area and clove in 1.67 ha area with the highest household income as much Rp. 196, 641 million per year.  Keywords: Community Forest, Linear Programming, Village Wongkai